1987
DOI: 10.1210/mend-1-1-97
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Inhibition of Tissue-Type Plasminogen Activator (tPA) Activity: Paradoxical Induction of Both tPA Antigen and Plasminogen Activator Inhibitor*

Abstract: Incubation of HTC rat hepatoma cells with the synthetic glucocorticoid dexamethasone rapidly inhibits plasminogen activator (PA) activity and reveals the presence of a specific PA inhibitor (PAI-1). To determine whether the hormonal inhibition of PA activity reflects a decrease in the amount of PA or an increased amount of the inhibitor, or both, we have assayed PA and PAI-1 immunologically. HTC PA was determined to be entirely of the tissue type (tPA), and both free and complexed antigen was quantified by a R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…The significance of the increase of tPA and uPA mRNA in osteoblasts when protein synthesis is inhibited is not yet clear. These results are relevant to other work that emphasizes the importance in the regulation of PA activity of the specific inhibitor, PAI-1 (Gelehrter et al, 1987;Seifert and Gelehrter, 1978;Andreasen et al, 1986Andreasen et al, , 1990Gelehrter, 1989, 1990). PAI-1 is bound to vitronectin in the extracellular matrix and retains its functional activity there (Mimuro et al, 1987;Sakata et al, 1988;Salonen et al, 1989), thereby limiting extracellular proteolysis.…”
Section: Discussionsupporting
confidence: 62%
“…The significance of the increase of tPA and uPA mRNA in osteoblasts when protein synthesis is inhibited is not yet clear. These results are relevant to other work that emphasizes the importance in the regulation of PA activity of the specific inhibitor, PAI-1 (Gelehrter et al, 1987;Seifert and Gelehrter, 1978;Andreasen et al, 1986Andreasen et al, , 1990Gelehrter, 1989, 1990). PAI-1 is bound to vitronectin in the extracellular matrix and retains its functional activity there (Mimuro et al, 1987;Sakata et al, 1988;Salonen et al, 1989), thereby limiting extracellular proteolysis.…”
Section: Discussionsupporting
confidence: 62%
“…Cell Culture-HTC cells were maintained in monolayer cultures as described previously (5). In preparation for experiments, cells were plated in 60-mm tissue culture dishes and grown to confluence.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that incubation with the synthetic glucocorticoid, dexamethasone, decreases HTC cell tPA activity by increasing PAI-1 mRNA and protein 5-10-fold, an effect that is entirely explained by an increase in PAI-1 gene transcription (5)(6)(7). In contrast, these cells respond to cyclic nucleotides with a dramatic (Ն50-fold) increase in tPA activity that is primarily the result of a decrease in PAI-1 mRNA and protein (8).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The expression of the components of the Pg-Pm system is modulated by the transcriptional regulation of a variety of hormones, such as corticosteroids [115,116] and gonadotrophins [117,118], and of cytokines [119][120][121][122] [140,141]. Since the cytokines and growth factors have many other effects on tumor growth and metastasis, it is difficult to interpret published findings if the components of the Pg-Pm system may act in concert with these factors.…”
Section: Regulatory Mechanismsmentioning
confidence: 99%